Becoming a data head : how to think, speak, and understand data science, statistics, and machine learning - Gutman, Alex J.; Goldmeier, Jordan (John Wiley & Sons Inc., 2021)
"In Becoming a Data Head: How to Think, Speak, and Understand Data Science, Statistics, and Machine Learning, award-winning data scientists Alex Gutman and Jordan Goldmeier pull back the curtain on data science and give you the language and tools necessary to talk and think critically about it. You'll learn how to: Think statistically and understand the role variation plays in your life and decision making. Speak intelligently and ask the right questions about the statistics and results you encounter in the workplace. Understand what's really going on with machine learning, text analytics, deep learning, and artificial intelligence. Avoid common pitfalls when working with and interpreting data. Becoming a Data Head is a complete guide for data science in the workplace: covering everything from the personalities you'll work with to the math behind the algorithms. The authors have spent years in data trenches and sought to create a fun, approachable, and eminently readable book. Anyone can become a Data Head - an active participant in data science, statistics, and machine learning. Whether you're a business professional, engineer, executive, or aspiring data scientist, this book is for you."--Publisher's description.
Keywords: Data mining.; Machine learning.; elektronické knihy; electronic books